Exploring Student Preferences for Counseling Modalities: Online vs. Face-to-Face in Islamic Higher Education Institutions - Awad, Faizah Binti; Muh. Shaleh; Rezki, Anita; Tonn-Meller, Horst (KONSELOR, 2025)
This study examines the factors that influence the use of online counselling services and the preferences of students in Islamic Higher Education Institutions (PTKI) in Kendari City, Indonesia.  The research addresses four critical concerns by employing a quantitative method and an explanatory approach:  (1) What are the preferences of students regarding online counselling?  (2) What is the method by which students and faculty at PTKI implement online counselling?  (3) What are the factors that influence students' decision to choose online counselling over in-person counselling?  and (4) What are the factors that support and hinder the utilisation of online counselling services?  Data were gathered from 214 pupils in three PTKIs using the Online Counselling Attitude Scale (OCAS).  The results suggest that students prefer online counselling primarily due to its time efficiency and accessibility.  Nevertheless, concerns persist regarding the loss of personal connection with counsellors and the confidentiality of their interactions.  These results emphasise the necessity for PTKI to enhance counsellor training and fortify its digital counselling infrastructure to guarantee the ethical and effective deliverance of online services.